Suspended silicon waveguides for long-wave infrared wavelengths - Soler Penadés, Jordi; Sánchez-Postigo, Alejandro; Nedeljkovic, Milos; Ortega-Moñux, Alejandro; Wanguemert-Pérez, Juan Gonzalo; Xu, Yolanda; Halir, Robert; Qu, Zhibo; Khokhar, Ali Z.; Osman, Ahmed; Cao, Wei; Littlejohns, Callum G.; et al. (Optica Publishing Group, 2018)
In this Letter, we report suspended silicon waveguides operating at a wavelength of 7.67 μm with a propagation loss of 3.1±0.3 dB/cm. To our knowledge, this is the first demonstration of low-loss silicon waveguides at such a long wavelength, with loss comparable to other platforms that use more exotic materials. The suspended Si waveguide core is supported by a sub-wavelength grating that provides lateral optical confinement while also allowing access to the buried oxide layer so that it can be wet etched using hydrofluoric acid. We also demonstrate low-loss waveguide bends and s-bends.
Keywords: Fotónica; silicon photonics; mid-infrared; waveguide; suspended silicon; suspended waveguide; subwavelength grating metamaterial